Population density, abundance and distribution of a critically endangered and endemic Philippine hanging parrot (Loriculus philippensis worcesteri) in Leyte Sab-a Basin Peatland, Eastern Visayas, Philippines - Fabella, Marianne Lovella KZ3 R. (2023)
The population of the endemic Philippine Hanging Parrot (Loriculus philippensis) is globally categorized as Least Concern, however nationally, it is already Critically Endangered. Here, the population and distribution of the subspecies L. p. worcesteri endemic within an understudied peatland habitat in Leyte were examined. A distance sampling method was employed to approximate the population density of L. p. worcesteri in the Leyte Sab-a Basin Peatland (LSBP). Using the Distance software, the population was estimated to be at 110, 166, and 49 in man-made coconut groves, natural lowland and the peat swamp forest (PSF), respectively. These three total sampling plots were characterized each based on forest types and were examined for strong positive correlation with the associated bird population density. Remarkably, this study confirmed the first record of occurrence of L. p. worcesteri not just within the peatland ecosystem, but within the peat swamp forest as well. Ultimately, the findings of this study supports the proposed LSBP as a Local Conservation Area.